EFEKTIVITAS PEMBELAJARAN BERBANTUAN GOOGLE MEET DITINJAU DARI MOTIVASI DAN HASIL BELAJAR SISWA SEKOLAH DASAR - Ari Nurweni; Kulsum Nur Hayati; Aminnudin Zuhairi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
Covid-19 pandemic had affected all segments of life, including education. Education which so far carried out face-to face has now been implemented virtually. The online learning model raises various problems, such as decreased motivation and students’ learning outcomes.Those problem can be solved by using distance learning technology, such as Google Meet. This study aims at determining the difference in motivation and students’ learning outcomes as well as testing the effectiveness of learning in the experimental class compared to the control one. This study was carried out with a quasi-experiment. The experiment class uses Google Meet, while the other uses WhatsApp. The population of this study was all students of Cepokjajar 2 Elementary School with a total of 294 students, while the sample was class 5A and 5B with 29 students on each other. The data analyzed by the Independent T-test to find the difference beetwen the experimental class and the control one, and the N-gain Score to determine the effectiveness of each class in developing students’ motivation and learning outcomes. The Independent T-test result shows that: 1) there are differences in learning motivation between the experimental and control class with the significance value of 0.009 < 0.05; 2) there are differences in learning outcomes between the experimental and control class with the significance value of 0.005 < 0.05; 3) learning in experimental class is more effective in increasing students’ motivation and learning outcomes than in control one.